FINANCIAL EXPLOITATION OF THE WORKING WIFE )A field study in the City of Mosul( - Ismail, Reem Abdel-Wahab; Mahmoud, Nbal Fawzi (Journal of Tikrit University for Humanities, 2020)
This study aims at exploring the extent to which the husband exploits his wife's salary in addition to identifying the family problems encountering the working women. The exploiting of the husband to the wife may influence the family's stability. Such problems are not restricted to the wife only, but they extend to the husband and the children as well as the stability system in the family. This study offers some valuable recommendations.The researchers have employed an analytical descriptive approach with a data consisting of (100) working women from the city of Mosul whom were selected intentionally. After surveying the resulted frequencies and the percentages, the study comes up with a set of remarkable conclusions mainly: Most of the working women are enforced by their husbands to spend money on home and their children and the husband leaves such responsibility . Most of the working women cannot spend their money without having a prior permission of their husbands. Working women are enforced to give a portion or all of the salary to the husband in order to mitigate the marital problems or to avoid the divorce. The husband takes the salary, because he feels he is stronger and more responsible than her thinking that wives do not know how to spend her salary. i.e. he knows how to spend in a better way . Wife may– according to the husband – spend money for some unnecessary things The study shows that the agreement between the conflicting wife and husband to divide the expenses is the best solution in order to mitigate their marital problems.